Genetic variability in gaillardia (Gaillardia pulchella) - TAMUT, OMEM; KULKARNI, BALAJI S; PATIL, SATHEESH R (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted to find out variation in various gaillardia (Gaillardia pulchella Foug). Germplasm collected from different parts of the country and evaluation of these germplasms for various horticultural important traits. Seeds of 20 germplasms were sown and transplanted at experimental unit of Department of Floriculture and Landscape Architecture, Kittur Rani Channamma College of Horticulture, Arabhavi, during 2012-2013. Experiment was laid out in randomized block design with three replications and observations were recorded in monthly intervals. Significant variations were observed among gaillardia germplasm for analysis of variance. The phenotypic coefficients of variation (PCV) were higher than those of genotypic coefficients of variation (GCV) for all the characters studied. High heritability with high genetic advance as per cent mean was observed for plant height, number of leaves, number of branches/plant, leaf area, chlorophyll, days taken for first flowering, flower yield/plant, flower yield/ha, seed yield/ plant, seed yield/ha, flower diameter, number of whorls/flower, number of petals/flower, stalk length, single flower weight and ten flower weight.